PEMANFAATAN INTERNET BAGI MASYARAKAT DESA UNTUK PENINGKATAN EKONOMI KELUARGA DESA KASERANGAN - Januriana, Andi Moch (Universitas Sultan Ageng Tirtayasa, 2022)
Utilization of the internet has entered various circles, all people can access the internet with acomputer or smart phone. The use of the internet among the public still tends to be only as amedium of entertainment such as playing games, social media and YouTube. In fact, the internet canproduce economic things such as selling online, becoming a youtuber, to marketing strategies toincrease revenue in the company's service sector. Likewise, the tendency of the people of KaseranganVillage, Kec. Pontang, Serang Regency, Banten, where the people still haven't optimized the internet.In this village, it is not difficult to access the internet, because apart from internet quota fromcellular operators in Kaserangan Village, there is a public wifi facility that can be accessed bybuying internet vouchers. In the use of public wifi, people only use it as entertainment facilities suchas playing games and using social media, this is justified by the Kaserangan Village Head, thataround the wifi access area, people often gather to just play games and use social media until dawn,so that it unconsciously affects on the economic development of the village. So the research in thiscommunity service activity aims to explore the problem of how to use the internet among theKaserangan Village community by carrying out seminar activities. The seminar activity plan thatwill be used as a research, namely with the following materials: 1. The benefits of the internet for allpeople in the world. 2. Provide insight into the use of the internet through online buying and sellingbusiness opportunities. 3. Directing the community to use Youtube as a source of income. 4. Guidingpeople in the dangers of the internet.